2021
DOI: 10.3389/fcell.2021.643712
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Consensus in the Repertoire of Hemocytes Identified in Drosophila

Abstract: The catalog of the Drosophila immune cells was until recently limited to three major cell types, based on morphology, function and few molecular markers. Three recent single cell studies highlight the presence of several subgroups, revealing a large diversity in the molecular signature of the larval immune cells. Since these studies rely on somewhat different experimental and analytical approaches, we here compare the datasets and identify eight common, robust subgroups associated to distinct functions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 92 publications
0
45
0
Order By: Relevance
“…Importantly though, the col-GAL4 lines pcol85 and GMR13A11 are not only expressed in blood cell progenitors present in the lymph gland posterior lobes but also in the PSC ( Benmimoun et al, 2012 ; Ghosh et al, 2015 ; Rodrigues et al, 2021 ). Moreover, recent single-cell RNA-seq analyses revealed that PSC-like cells expressing col and Antp are present in circulating larval blood cells ( Cattenoz et al, 2021 ). Hence, these putative adult hematopoietic progenitors could have diverse origins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly though, the col-GAL4 lines pcol85 and GMR13A11 are not only expressed in blood cell progenitors present in the lymph gland posterior lobes but also in the PSC ( Benmimoun et al, 2012 ; Ghosh et al, 2015 ; Rodrigues et al, 2021 ). Moreover, recent single-cell RNA-seq analyses revealed that PSC-like cells expressing col and Antp are present in circulating larval blood cells ( Cattenoz et al, 2021 ). Hence, these putative adult hematopoietic progenitors could have diverse origins.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, differentiated larval plasmatocytes can not only proliferate but also transdifferentiate into crystal cells ( Makhijani et al, 2011 ; Leitao and Sucena, 2015 ), and it was proposed that the increase in peripheral blood cells during larval development relies on self-renewing plasmatocytes ( Gold and Bruckner, 2015 ). Yet, undifferentiated blood cells were also described among peripheral hemocytes ( Sinenko et al, 2010 ) and recent single-cell sequencing experiments suggest that proliferative plasmatocytes retain a progenitor signature ( Cattenoz et al, 2020 , 2021 ; Tattikota et al, 2020 ). In parallel, a second wave of hematopoiesis takes place during the larval stages in a specialized organ called the lymph gland ( Lanot et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Insects as Food and Feed categorise entities on a continuous scale into discrete categories (Cattenoz et al, 2021;Fu et al, 2020;Tattikota et al, 2020).…”
Section: Please Cite This Article As 'In Press'mentioning
confidence: 99%
“…Importantly though, the col-GAL4 lines pcol85 and GMR13A11 are not only expressed in blood cell progenitors present in the lymph gland posterior lobes but also in the PSC (Benmimoun et al, 2012; Ghosh et al, 2015; Rodrigues et al, 2021). Moreover, recent single-cell RNA-seq analyses revealed that PSC-like cells expressing col and Antp are present in circulating larval blood cells (Cattenoz et al, 2021). Hence, these putative adult hematopoietic progenitors could have diverse origin.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, differentiated larval plasmatocytes can not only proliferate but also transdifferentiate into crystal cells (Leitao and Sucena, 2015; Makhijani et al, 2011), and it was proposed that the increase in peripheral blood cells during larval development relies on self-renewing plasmatocytes (Gold and Bruckner, 2015). Yet, undifferentiated blood cells were also described among peripheral hemocytes (Sinenko et al, 2010) and recent single-cell sequencing experiments suggest that proliferative plasmatocytes retain a progenitor signature (Cattenoz et al, 2021; Cattenoz et al, 2020; Tattikota et al, 2020). In parallel, a second wave of hematopoiesis takes place during the larval stages in a specialized organ called the lymph gland (Lanot et al, 2001).…”
Section: Introductionmentioning
confidence: 99%